The effect of patent ductus arteriosus on pre-ductal and post-ductal perfusion index in preterm neonates. (19th July 2018) - Nitzan, Itamar; Hammerman, Cathy; Fink, Daniel; Nitzan, Meir; Koppel, Robert; Bromiker, Ruben
Abstract: Objective : The ductus arteriosus is a blood vessel that connects the pulmonary artery to the descending aorta during fetal life and generally undergoes spontaneous closure shortly after birth. In premature neonates it often fails to close (patent ductus arteriosus—PDA), which can result in diversion of a significant part of the left-ventricular cardiac output to the pulmonary circulation. This left-to-right shunt may result in significant increase of pulmonary blood flow and decrease of systemic perfusion (hemodynamically significant PDA—hsPDA), which may lead to severe neonatal morbidity. The study objective was to find the relationship between hsPDA and perfusion index (PI), a photoplethysmographic parameter related to systemic perfusion. Approach : PI measures the relative systolic increase in tissue light absorption due to the systolic increase in the tissue blood volume. PI has been found to be directly related to tissue perfusion and is therefore expected to be affected by hsPDA. Main results : PI was found to be higher in preterm neonates with hsPDA after first week of life, in comparison to those with closed DA, despite the lower systemic perfusion, probably due to reverse flow during diastole. Significance : In our study, perfusion index increased despite the lower systemic perfusion, indicating that in neonates with hsPDA, perfusion index is not necessarily a measure of perfusion. Nevertheless, PI can be used as a screening tool for suspicious PDA, in order to select a relatively small group of neonates for a more definitive examination by echocardiography, which is not suitable for universal screening.